Determining the rate of follow-up after hospital emergency department visits for dental conditions - Meyer, Beau (Clin Cosmet Investig Dent, 2016)
BACKGROUND: Emergency department (ED) visits for dental reasons continue to impact EDs nationwide. This investigation determined the rate of follow-up in an emergency dental clinic (EDC) after hospital ED visits for nontraumatic dental conditions. METHODS: This prospective investigation reports the number of patients who presented to an ED for nontraumatic dental conditions and the rate of follow-up at an EDC. Upon ED discharge, patients were provided instructions to follow-up for low-cost care at the EDC. Telephone contact was attempted following failed referrals. Descriptive statistics were reported for comparing referral sources and demographic trends. RESULTS: Two hundred and forty-seven referrals were made and 31% followed up for definitive treatment at the EDC. More referrals were made on weekends than on weekdays. Failed referrals were unreachable by telephone in 75% of cases. Tooth extraction was the most common treatment rendered in the EDC. Of the ED patients who accessed EDC care, 14% became comprehensive patients in the EDC’s regular dental clinic. CONCLUSION: Less than one-third of ED referrals to the EDC followed up for definitive care when provided an opportunity to do so, and 75% of referrals were unreachable by telephone in the week following the ED dental visit.